2017
DOI: 10.2967/jnumed.116.185991
|View full text |Cite
|
Sign up to set email alerts
|

Arterial CO2 as a Potent Coronary Vasodilator: A Preclinical PET/MR Validation Study with Implications for Cardiac Stress Testing

Abstract: Myocardial blood flow (MBF) is the critical determinant of cardiac function. However, its response to increases in partial pressure of arterial CO 2 (PaCO 2 ), particularly with respect to adenosine, is not well characterized because of challenges in blood gas control and limited availability of validated approaches to ascertain MBF in vivo. Methods: By prospectively and independently controlling PaCO 2 and combining it with 13 N-ammonia PET measurements, we investigated whether a physiologically tolerable hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
3
18
2
Order By: Relevance
“…Studies in canines demonstrated the dynamic response of MBF over a range of 30-60 mm Hg. More recently, Yang et al showed no significant difference between the responses to hypercapnia and adenosine infusion in canines without coronary stenosis, with MBF doubling over that at baseline (8).…”
mentioning
confidence: 98%
“…Studies in canines demonstrated the dynamic response of MBF over a range of 30-60 mm Hg. More recently, Yang et al showed no significant difference between the responses to hypercapnia and adenosine infusion in canines without coronary stenosis, with MBF doubling over that at baseline (8).…”
mentioning
confidence: 98%
“…The effect of carbon dioxide seems to be similar with those exert by carbon monoxide and nitric oxide, inducing vasodilatation associated with smooth cells proliferation reduction, and having an inhibitor effect on platelets aggregation [14,15]. In vivo animal studies with coronary vessels vasoconstriction follow by stenosis (induced by caffeine), vasodilatation effect activity of carbon dioxide was demonstrated with significantly improved coronary blood flow (PET studies of the heart) [16]. The oxidative stress contribution to ischemia has been intensively studied, with a special attention given to quantitative assessment of oxidative stress parameters and their relationship with the ischemia progression and consequences.…”
Section: Histopathology Assessment Resultsmentioning
confidence: 99%
“…All animals were studied according to the NIH "Guide for the Care and Use of Laboratory Animals" following approval of Institutional Animal Care and Use Committee. In a subset of the animals, a left lateral thoracotomy was performed as previously described by our group (22). A Doppler probe was attached distal to the first branch of the left anterior descending coronary artery (LAD) to enable measurement of coronary blood flow velocity (CBFV).…”
Section: Animal Preparation and Methods For Inducing Coronary Stenosismentioning
confidence: 99%
“…The proposed method builds on previous studies from our laboratory and elsewhere, which show that tolerable levels of hypercapnia leads to more than 2-fold increase in myocardial blood flow and similar modulation in oxygenation in extent to that observed with adenosine (commonly used coronary vasodilator) in both in dogs and in humans (22) (28). Although our findings in this study are limited to canines, given that all cardiac stress testing paradigms have been first successfully demonstrated in dogs, and 25-mmgHg increase in PaCO2 is tolerable in humans, we anticipate that the proposed approach would translate well in humans.…”
Section: Practical Aspects Of Translating the Proposed Approach Into mentioning
confidence: 96%
See 1 more Smart Citation